2022
DOI: 10.1002/glr2.12038
|View full text |Cite
|
Sign up to set email alerts
|

Improving bermudagrass in the Southeastern United States with alfalfa as an alternative nitrogen source in grazing systems

Abstract: Background Bermudagrass (Cynodon spp.) is one of the most common perennial warm‐season forages grown in the Southeastern United States. The incorporation of alfalfa (Medicago sativa) into bermudagrass pastures could serve as an alternative source of nitrogen (N) while also improving the nutritive value of the forage base. Methods A 2‐year grazing evaluation arranged in a randomized complete block design was conducted from May to September 2018 (Year 1) and May–August 2019 (Year 2) in Tifton, GA, USA. The objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 47 publications
2
13
2
Order By: Relevance
“…Overall, the reported TDN values from both locations were comparable to Beck et al (2017b), Hendricks et al (2020) for ABG mixtures harvested for grazing or stored forage on a 28-35 days HF. Conversely, the TDN values of the current evaluation for both the HH and HF treatments are greater than those reported by Burt et al (2022) and Rushing et al (2022) for ABG mixtures (both approximately 55% TDN).…”
Section: Nutritive Valuecontrasting
confidence: 84%
See 4 more Smart Citations
“…Overall, the reported TDN values from both locations were comparable to Beck et al (2017b), Hendricks et al (2020) for ABG mixtures harvested for grazing or stored forage on a 28-35 days HF. Conversely, the TDN values of the current evaluation for both the HH and HF treatments are greater than those reported by Burt et al (2022) and Rushing et al (2022) for ABG mixtures (both approximately 55% TDN).…”
Section: Nutritive Valuecontrasting
confidence: 84%
“…It is not surprising that the observed CP from the Alabama samples was numerically greater than those reported in Georgia considering the difference in the alfalfa content discussed in the previous section. Despite the differences in the alfalfa component in the stand for both locations, the observed CP for both locations was greater than those reported by Marks (2020), Burt et al (2022), andHarling et al (2023) for ABG mixtures. In contrast, Beck et al (2017b) and Hendricks et al (2020) observed higher CP values than those in the current study at both locations.…”
Section: Nutritive Valuecontrasting
confidence: 73%
See 3 more Smart Citations